HOXA-AS2 may be a potential prognostic biomarker in human cancers: A meta-analysis and bioinformatics analysis - Zhang, Fan; Zhang, Guangming; Zhang, Helin; Pu, Xingyu; Chi, Fei; Zhang, Dengxiao; Xin, Xiaoming; Gao, Mingxuan; Luo, Wenyuan; Li, Xingyong (Frontiers in Genetics, 2022)
Background: Dysregulation of long non-coding (lncRNA) has been reported in various solid tumors. HOXA cluster antisense RNA 2 (HOXA-AS2) is a newly identified lncRNA with abnormal expression in several human malignancies. However, its prognostic value remains controversial. This meta-analysis synthesized available data to clarify the association between HOXA-AS2 expression levels and clinical prognosis in multiple cancers. Methods: Four public databases (Embase, PubMed, Web of Science, The Cochrane Library) were used to identify eligible studies. Hazard ratios (HRs) and odds ratios (ORs) with their 95% confidence intervals (CIs) were combined to assess the correlation of HOXA-AS2 expression with survival outcomes and clinicopathological features of cancer patients. Publication bias was measured using Begg’s funnel plot and Egger’s regression test, and the stability of the combined results was measured using sensitivity analysis. Additionally, multiple public databases were screened and extracted to validate the results of this meta-analysis. Results: The study included 20 studies, containing 1331 patients. The meta-analysis showed that the overexpression of HOXA-AS2 was associated with poor overall survival (HR = 2.06, 95% CI 1.58–2.69, p < 0.001). In addition, the high expression of HOXA-AS2 could forecast advanced tumor stage (OR = 3.89, 95% CI 2.90–5.21, p < 0.001), earlier lymph node metastasis (LNM) (OR = 3.48, 95% CI 2.29–5.29, p < 0.001), larger tumor size (OR = 2.36, 95% CI 1.52–3.66, p < 0.001) and earlier distant metastasis (DM) (OR = 3.54, 95% CI 2.00–6.28, p < 0.001). However, other clinicopathological features, including age (OR = 1.09, 95% CI 0.86–1.38, p = 0.467), gender (OR = 0.92, 95% CI 0.72–1.18, p = 0.496), depth of invasion (OR = 2.13, 95% CI 0.77–5.90, p = 0.146) and differentiation (OR = 1.02, 95% CI 0.65–1.59, p = 0.945) were not significantly different from HOXA-AS2 expression. Conclusions: Our study showed that the overexpression of HOXA-AS2 was related to poor overall survival and clinicopathological features. HOXA-AS2 may serve as a potential prognostic indicator and therapeutic target for tumor treatment.